A Doubly Green Separation Process: Merging Aqueous Two-Phase Extraction and Supercritical Fluid Extraction - Andrey Voshkin (Processes, 2021)
Aqueous two-phase extraction (ATPE) is a green separation technique which uses mixtures of water and environmentally benign polymers such as polyethylene glycol (PEG) as solvents. One of the challenges in implementing this extraction on an industrial scale is finding a suitable method for the isolation of target compounds from water-polymer solutions after the extraction, without diminishing ecological benefits of the method. In this paper, we propose using another green separation technique, supercritical fluid extraction (SFE), for the back-extraction of low molecular weight medium polarity compounds from ATPE solutions. Experiments with two model compounds, caffeine and benzoic acid, showed principal applicability of SFE for this task. Pressure (100–300 bar) and temperature (35–75 °C) of supercritical carbon dioxide play a major role in defining extraction capability. Extraction ratios of 35% for caffeine and 42% for benzoic acid were obtained at high fluid pressure and moderate temperature at 1:6 volume phase ratio. That gives an estimation of 10–20 theoretical steps required for complete exhaustive extraction from the ATPE solution, which is readily achievable in standard counter-current column SFE. Combining these two green methods together not only serves as an environmentally friendly method for the isolation of valuable low molecular weight compounds from diluted water solutions, but also allows for simple, energy effective recuperation of ATPE solvents.